Benthic–Pelagic Coupling in the Oligotrophic Eastern Mediterranean: A Synthesis of the HYPOXIA Project Results - Dimitriou, Panagiotis D.; Santi, Ioulia; Moraitis, Manos L.; Tsikopoulou, Irini; Pitta, Paraskevi; Karakassis, Ioannis (Frontiers in Marine Science, 2022)
Benthic–pelagic coupling studies have shown that the response of the benthic system to eutrophication is subject to complex nonlinear dynamics with specific thresholds beyond which abrupt changes in the response of the ecosystem occur and time lags between inputs and responses. The “HYPOXIA: Benthic–pelagic coupling and regime shifts” project aimed to investigate how nutrient input in the water column results in ecological processes of eutrophication, which may lead to significant, irreversible changes in the eastern Mediterranean marine ecosystems within a short period of time. The project included analysis of historical water and benthic data, field sampling, and mesocosm experiments. From the project results, it can be concluded that nutrient inputs are quickly capitalized by small phytoplankton species in the water column resulting in the bloom of specific species with high nutrient uptake capabilities. When Eutrophic Index values (calculated using nutrient and chlorophyll-a concentrations) cross the moderate-to-poor threshold, the precipitating organic matter can cause observable effects on the benthic system. Depending on eutrophication intensity and persistence, the effects can start from microbenthos, meiofauna, and macrofauna increase in abundance and biomass to significant changes in the community structure. The latter includes the proliferation of macrofaunal opportunistic species, an increase in deposit feeders, and the high risk of ecosystem quality degradation. However, contrary to other regions of the world, no water hypoxia or benthic dead zones were observed as chlorophyll-a and O2 concentrations showed a positive correlation. This is caused by the high photosynthetic activity of the phytoplankton and microphytobenthos, the increased bioturbation of macrofauna, and the increased abundance of sediment deposit-feeding species, which quickly consume the excess organic matter. Eastern Mediterranean coastal ecosystems show high resilience to the adverse effects of eutrophication, preventing hypoxia and azoic conditions when eutrophication is the only source of environmental disturbance.